Implementation of Clustering Techniques in Various Fields: A Survey - Zishan Ali, Syed; Chundawat, Surbhi; Shukla, Shrinjanee; Choudhary, Akshat (International Journal of Computer Sciences and Engineering, 2019)
In Today’s world clustering techniques are used in different fields like Image Classification, AI, E-commerce, etc. The advantage of clustering is that it provides a summarized output for the user, where the user can obtain the exact results and predict the outcome. Once implemented, clustering offers a clarified outcome to the user which strikes out the necessity for further research and development. Clustering plays a major role in areas where there is a probability and necessity of figuring out similar as well as dissimilar objects. One of the major aspects of data mining is to differentiate between objects based on their properties or attributes. This paper focuses on three such fields namely Medical Science, Agriculture and E-Commerce.